Effects of precipitation variability and conservation tillage on soil moisture, yield and quality of silage maize - Niu, Lili; Qin, Wangfei; You, Yongliang; Mo, Qishun; Pan, Jie; Tian, Lihua; Xu, Guang; Chen, Chao; Li, Zhou (Frontiers in Sustainable Food Systems, 2023)
To cope with the change of precipitation pattern, we explored the effects of conservation tillage and precipitation variability on soil moisture status and silage maize productivity, seeking solutions to improve the yield and quality of maize in the karst areas of China. In this study, precipitation variability and conservation tillage were jointly analyzed by precipitation levels (normal precipitation, 30% lower and 30% greater than normal precipitation), tillage methods (conventional tillage and no-tillage) and cover crop mulching (mulching and no mulching). It was found that no tillage (NT) increased the maize yield by 12.85% compared with the conventional tillage (CT) treatments. Above-normal precipitation treatments did not significantly increase biomass and soil water content across different fertility stages, but below-normal precipitation treatments reduced maize yield, crude protein (CP) content and soil water content at all soil levels. CT treatment significantly increased soil water content in the tillage layer (0–40 cm), but NT treatment significantly increased dry matter yield, plant height and CP content at harvest by 10.99, 3.41, 5.62%. Cover crop mulching significantly increased maize yield by 8.26% and soil moisture content at the seedling stage in 0–40 cm soil by 2.76 and 2.52%. The three-way interaction effects involving precipitation levels, tillage methods and cover crop mulching were significant for maize yield, CP content and soil water content (p < 0.05). In addition, this study found that soil water content was positively correlated with crude protein content of maize (p < 0.05). In conclusion, this study concluded that a combination of NT and cover crop mulching should be used to mitigate maize production risks caused by precipitation variability in the karst areas.